Praktische Theologie : Zeitschrift für Praxis in Kirche, Gesellschaft und Kultur (Gütersloher Verlagshaus, 1966)
Praktische Theologie is a journal for theological practitioners wishing to reflect their professional domains, such as pastoral ministry, professional training, school, adult education, the social realm, and others, on a scholarly basis. It covers current topics in the area of religion and society, specific challenges within the professional domains named above, and topics from the fields of human and social science relevant for competent professional practice. Each issue features a central topic with experiences, reports, and practical-theological as well as socio-scientific analyses of its various aspects. Historical background information, reviews and literature reports complement each issue. ---------- PRINT available from Gütersloher Verlagshaus:http://www.fachzeitschriften-religion.de/praktische-theologie